The 2D Structure of the T. brucei Preedited RPS12 mRNA Is Not Affected by Macromolecular Crowding - Leeder, W.-Matthias; Voskuhl, Stephan; Göringer, H. Ulrich (Journal of Nucleic Acids, 2017)
Mitochondrial transcript maturation in African trypanosomes requires RNA editing to convert sequence-deficient pre-mRNAs into translatable mRNAs. The different pre-mRNAs have been shown to adopt highly stable 2D folds; however, it is not known whether these structures resemble the in vivo folds given the extreme “crowding” conditions within the mitochondrion. Here, we analyze the effects of macromolecular crowding on the structure of the mitochondrial RPS12 pre-mRNA. We use high molecular mass polyethylene glycol as a macromolecular cosolute and monitor the structure of the RNA globally and with nucleotide resolution. We demonstrate that crowding has no impact on the 2D fold and we conclude that the MFE structure in dilute solvent conditions represents a good proxy for the folding of the pre-mRNA in its mitochondrial solvent context.